FINANCIAL TECHNOLOGY PADA PELAKU UMKM: STUDI TENTANG PERSEPSI MANFAAT, PERSEPSI KEMUDAHAN SERTA KEPERCAYAAN TERHADAP PENGGUNAAN STARTUP OVO - Rifa'i, Muhamad; Yanti, Dyah Agustin Widhi; Handayati, Ratna (Bisma: Jurnal Bisnis dan Manajemen, 2023)
Financial technology is a service that is in great demand in today's society. OVO is a financial technology startup which provides electronic wallet service. The presence of OVO as a financial technology service has attracted the attention and interest of the community because of the ease of its transaction function. This study aimed to determine the effect of benefits, convenience, and confidence of micro, small, and medium enterprises on interest in using financial technology. This research was conducted using a quantitative approach. The research sample was determined using the sampling estimation method, and the sample size of 96 respondents was determined using the Lemeshow formula. Data collection techniques were conducted through questionnaires. The collected data were then analyzed using multiple linear regression techniques. The results showed that perceived benefits, perceived comfort, and business needs significantly affected interest in using financial technology.